Child Marriage in Bangladesh: Policy and Ethics (Bangladesh Journal of Bioethics, 2020)
Bangladesh is a Muslim-majority society with more than 163 million people. Most Bangladeshis hold the ideals of Islamic norms and values which is manifest in all sorts of socio-cultural behaviour. In reference to such values, the tradition of legitimizing child marriage in Bangladesh is the issue that needs to be addressed in a holistic yet rigorous approach. Currently Bangladesh ranks 4th in the world and 1st in Asia in terms of child marriage. Recently the Child Marriage Restraint Act 1929 has been abolished and it has been replaced by the Act of 2017 preserving article 2 of the previous statute, the legal age for marriage for a boy 21 and for a girl 18. This Act adds article 19 which legalizes minors (below 18 years of age) to be married off with the consent of the parents/guardians at the presence of a magistrate under “special circumstances” deemed with securing the best interest for them. The law artfully coincides with the Muslim Marriage Law which allows participants of 15 years and above to get legally married and as such contradicts the international law and the Act of 2017 itself. In the West intimate relationships including extra-marital cohabitation before reaching 18 years of age are culturally accepted. In contrast, such extra-marital and intimate relationships are strictly prohibited in Muslim-majority societies, which are dearly adhered in Bangladeshi Muslim culture. This study examines how the religious cultural and socio-economic realities influence child marriage practice in Bangladesh. Along with secondary documents, we interviewed 22 individuals including the Deputy Commissioner, the District Women and Children Affairs Officer, elected Union Parishad Chairman and Members, Social Workers, married couples and their parents/guardians at Manikganj district. In addition, we also conducted a mass survey with 62 randomly selected participants, and a voluntary online survey where the opinion of another 53 young students were collected to find broad opinion. We also collected stories of how marriages take place at the rural, urban and sub-urban areas in Bangladesh. The study has revealed that Bangladeshis does not support marriage at early ages but socio-economic reality often pushes poor into getting their children married at early ages. Many view that the special provision may encourage child marriage in the country. This study suggests that the government of Bangladesh should redefine public policy in regard to finding a middle ground between Islamic ethics and international values by exploring isomorphic mimicry and other socio-culturally accepted measures with a view to abolishing child marriage successfully.